Integrasi Health Policy Triangle dan Prinsip Good Governance dalam Program PKRS untuk Mendorong Perubahan Perilaku Kesehatan Pasien : Suatu Tinjauan Sistematik - Yasinta Indah Widyaningsih; Nurfalia Harfah; Azharatul Jannah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Health policy and hospital governance integration is essential in strengthening hospital-based health promotion, particularly through the Health Promotion Hospital Program (PKRS). This systematic review aims to analyze literature on practices, challenges, and strategies for aligning health policy and administrative governance in improving the effectiveness of behavioral-based health promotion in hospitals. The review was conducted using the Health Policy Triangle framework and Good Governance principles to identify how policy, actors, and context interact in shaping sustainable behavioral change interventions. Articles were retrieved from Scopus, ScienceDirect, and Google Scholar databases using the keywords “health policy synergy,” “hospital governance,” “behavioral-based health promotion,” and “administrative integration.” Inclusion criteria included studies from 2020–2025 focusing on hospital-based health promotion, governance mechanisms, and digital transformation in behavioral change management. The synthesis revealed that behavioral health promotion effectiveness depends on adaptive policy integration, transparent governance, digital transformation, and human resource capacity building. Strengthening PKRS implementation requires evidence-based policies, innovative governance, and digital systems that support real-time data, cross-sector collaboration, and participatory decision-making. In conclusion, the integration of the Health Policy Triangle and Good Governance principles enhances hospital accountability, communication, and efficiency, thereby fostering sustained behavioral change and advancing national health goals.